Cloud-aided online/offline ciphertext-policy attribute-based encryption in the standard model. (2017) - Wang, Hao; Zheng, Zhihua; Wang, Yilei
Attribute-Based Encryption (ABE) is a useful encryption method that allows users to encrypt messages based on their attributes. However, the computational cost of ABE system is very high, because it often scales with the number of attributes. This makes ABE difficult to apply in practice. In this paper, we use the cloud computing technology as well as pre-computing technology to solve this problem, and introduce the cloud-aided online/offline ciphertext-policy ABE system. In this system, Private Key Generator (PKG) could per-compute intermediate keys offline before online key generation phase, encryptor could pre-compute intermediate ciphertexts offline before online encryption phase, and decryptor could call their cloud computing servers to transform the ciphertexts to the partially decrypted ciphertexts before decryption phase. This greatly reduces the local computational cost of these three phases. It is significant for mobile devices to use ABE. Then, we propose a specific scheme, and prove its adaptive security in the standard model. Finally, we introduce how to deploy our new scheme in the mobile cloud computing environment.